Сын ярла - Посняков Андрей (Новые супергерои, 2011)
Экземпляры: ф.6 (2013) / Инвентарный номер: 55051 / Цена: 161.70 / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 62 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44